Effectiveness of a community health worker-led low-sodium salt intervention to reduce blood pressure in rural Bangladesh: protocol for a cluster randomized controlled trial - Chang, Andrew; Rahman, Mushfiqur; Talukder, Animesh; Shah, Humyra; Mridha, Malay Kanti; Hasan, Mehedi; Sarker, Malabika; Geldsetzer, Pascal (Trials, 2023)
Background: High blood pressure is a major public health problem in low- and middle-income countries. Low-sodium salt substitute (LSSS) is a promising population-level blood pressure-lowering intervention requiring minimal behavioral change. The optimal method of delivering LSSS to individuals, however, is currently unknown. Community health workers (CHWs) have successfully been used to implement health interventions in Bangladesh and may provide a venue for the dissemination of LSSS. Methods: We aim to conduct a cluster-randomized controlled trial involving 309 households in rural Bangladesh previously identified and characterized by the BRAC James P Grant School of Public Health, BRAC University (BRAC JPGSPH). These households will be randomly assigned to three arms: (1) control, i.e., no intervention; (2) information only, i.e., community health workers will provide basic information on high blood pressure, the health consequences of excessive salt consumption, and feedback to the participant on the likely quantity of salt s/he consumes (estimated using a questionnaire); (3) free LSSS arm: the same information as in arm 2 will be provided, but participants will receive 6 months of free low-sodium salt along with education on the benefits of LSSS. One male and one female adult (age ≥ 18 years) in each household will be invited to participate, the exclusion criteria being households with members known to have high serum potassium levels, are taking medications known to elevate potassium levels (e.g., ACE inhibitors, ARBs, potassium-sparing diuretics), are already taking potassium supplements, or those who have known kidney disease or abnormal serum creatinine at baseline. The primary endpoint will be blood pressure at 6 months post-intervention. Discussion: Recent large clinical trials of LSSS in China and India have shown not only blood pressure improvements, but also stroke, major cardiac event, and all-cause mortality reductions. Nevertheless, how to best translate this intervention to population-level effectiveness remains unclear. Our study would test whether a community health worker-based program could be effectively used to disseminate LSSS and achieve measurable blood pressure benefits.
Veröffentlicht: 27. Juli 2023
Gesehen am 02.10.2023